The life of reason, or, The phases of human progress - Santayana, George, 1863-1952 (Santayana, George, 1863-1952. Works. 1986)
Influential philosopher, poet, and literary critic George Santayana (1863-1952) was a thorough naturalist, concerned with the ideal factors in human experience. He held that everything possesses a natural basis and that everything natural has an ideal development. In this one-volume edition of his early work, The Life of Reason (originally published 1905-6), Santayana argues that rational life is embodied in various ideal forms, including religion, and that religion may be embodied in reason. However, this is not to say that religion is grounded in science; rather, religion is poetic, a rendering of natural events in a dramatic form. Hence, to take so-called religious truths as literal claims is preposterous.